Palladium Catalyzed Reactions of 2-Nitroaniline with Vinylethers - Farideh Piri; Mina Behrouzi Fard Moghaddama; Babak Karimi (E-Journal of Chemistry)
A new method for the synthesis of hemiaminal ether have been suggested. The reactions of 2-nitro aniline with vinyl ether in the presence of PdCl2(CH3CN)2 produces hemiaminal ether compounds. The resulting products have been identified by spectral data.